Raija Hurme, Maritta Pesonen & Olli Syvlioja: Englanti-Suomi opiskelusanakirja ('Engelsk-finsk studieordbok') - Sarvas, Leena (LexicoNordica, 1995)
Anmeldt værk: Raija Hurme, Maritta Pesonen, Olli Syvaoja: Englanti-Suomi opiskelusanakirja ('Engelsk-finsk studieordbok'). WSOY, Juva 1994. Pris 157 FIM. In this contribution, the author examiries a new medium-sized English-Finnish dictionary by putting it in a user's test. Comparisons are made with a large bilingual dictionary compiled by the same authors. The inclusion of new words in some special quickly developing fields and slang, the handy size of the book, as well as the outlay and setting of the head words are positive features of the work. Tue author reminds of the structural differences of the languages involved and is more critical towards the pragmatic way of classifying some words, primarily adjectives: in some cases subarticles with examples of contexts would be preferable. She would also like to have a preface with more information on the sources and theoretical principles of the work.